2017
DOI: 10.1097/mnm.0000000000000684
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of lutetium-177-labeled stannous (tin) colloid for radiosynovectomy

Abstract: Lu-Sn colloid was successfully prepared with a high LE (>95%) and high RCP (99%) under optimized reaction conditions. Because of the numerous benefits of Lu and the ease of preparation of tin colloid particles, Lu-Sn colloid particles are significantly superior to its currently available counterparts for use in radiosynovectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In our experimental studies, temperature was kept constant since the reaction of 225 Actinium with various precursors was well performed between 90˚C -100˚C [15] [21] [31]. Recently, Arora et al [32] has successfully demonstrated that optimum labeling efficiency of 177 1). We assume that 0.18 mCi could be quite high amount of activity for the possible applications of further preclinical/clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…In our experimental studies, temperature was kept constant since the reaction of 225 Actinium with various precursors was well performed between 90˚C -100˚C [15] [21] [31]. Recently, Arora et al [32] has successfully demonstrated that optimum labeling efficiency of 177 1). We assume that 0.18 mCi could be quite high amount of activity for the possible applications of further preclinical/clinical trials.…”
Section: Resultsmentioning
confidence: 99%